Direct deposition of Cu/barrier stacks on dielectric/nonconductive layers using supercritical CO/sub 2 - Kondoh, E.; Hishikawa, M.; Yanagihara, M.; Shigama, K. (Proceedings of the IEEE 2004 International Interconnect Technology Conference : Hyatt Regency Hotel, Burlingame, CA, June 7-9, 2004, 2004)
Metallization in supercritical CO/sub 2/ (scCO/sub 2/) is a method to form nano-interconnects for future generation LSIs. It has been recognized that metal layers, Cu for instance, grow only on conductive layers thus requires an underlayer or 'activation' treatment to promote nucleation. Such a layer is formed by a conventional way, which may limit the potential of scCO/sub 2/ deposition. The keys to solve this issues are: 1) to develop a way to deposit a conductive barrier layer, and 2) to develop a proper chemistry to deposit the barrier layer directly on dielectric/nonconductive layers from scCO/sub 2/. The focus of this work is to form Cu/barrier stacks on dielectric layers using only scCO/sub 2/.